Between family and market: the decline of professional employment among Egyptian female university graduates - Aboul Ela, Magda (AUC Knowledge Fountain, 2012)
It is noticeable that the female professional employment is declining among graduate students in Egypt. The patriarchal gendered attitudes permeate family, labor market and state to form a powerful obstacle to women's equal participation in the labor market. The young women struggle to position themselves in the labor market without institutional or structural coverage. On one hand the patriarchal family reinforces the gender norms that dictate the secondary status of women whether at the household or in the labor market and moreover, preaches the male dominance ideology. On the other hand the state's legislation deepens this secondary status of women be reinforcing that women's first responsibility is their families'. Furthermore, the employers as producers and bearers of gender norms apply firing and hiring practices and procedures that strengthen the male dominance ideology in the labor market. Young women in their trial to join the labor market struggle the gendered societal norms and the neoliberal economic system and the Structured Adjusted Programs adopted since the 1990s. These programs failed to create suitable jobs for the skilled, qualified female to compensate the freezing of the public sector as the previous main employer of women in Egypt in Nasser's era and before Sadat's â Open doorâ policy. Moreover, neoliberal programs are non gender sensitive as they failed to accommodate women's production activity with their reproduction activities. The study adopted feminist perspective to frame the question of the decline of the professional employment among young women university graduates with case studies of students and graduates of Computer Science and Engineering at the American University in Cairo. Such a perspective allows access the barriers between subjectivity and objectivity; guarantees diversity and enables studying the articulation between neopartriarchy and neoliberalism in causing the phenomenon. The findings of the research indicated the importance of the private life over the business careers of the young women and the identification of women with domestic activities as natural and moral assignment. It also asserted the stagnation of the gender relations due to the failure of the economic development and the articulation between the gendered state and neopatriarchal Islamists. The research also remarks the failure of bargaining ability among the young women that extends to the labor market. The research calls for social transformation rather than just improving public services. My research aspires to contribute to a positive social change in the position of women in Egypt and to adopt social policy that promotes gender equality and advocates work as a human right.